THE CURRENT STATE OF THE PROBLEM OF SOCIAL AND PSYCHOLOGICAL READINESS OF YOUNG PEOPLE TO VOLUNTEERING - Galina Efremova; Angelina Shagurova; Irina Bochkovskaya (Вестник Северо-Кавказского федерального университета)
The article analyzes the socio-psychological readiness of young people to volunteer activities. In the pilot study shows that the desire and the desire of the person to participate in the volunteer movement is not correlated with the degree of its social and psychological readiness for volunteer activities. The involvement of today's youth in volunteer activities, and their willingness and desire to participate in charity events and volunteer corps determined various features of value-semantic and need-motivational sphere ofpersonality: in addition to the values of humanity and altruism, mutual aid and charity motifs entry into the volunteer movement and are needs of the individual to satisfy their own selfish ambitions, and focus on the power, and the need for self-realization and self-affirmation, to compensate the socio-situational and private potrebnostnoj dissatisfaction.